210k views
0 votes
HELLO, I NEED HELP ASAP :(

Use the distributive property to write the sum as a product.
(-1)·2+(-1)·ₓ

2 Answers

5 votes

Answer:

(-1)·2+(-1)·ₓ = -1 (2+x)

Explanation:

distributive property: ab +ac = a(b+c)

in this case a=-1, b =2, c =x so

(-1)·2+(-1)·ₓ = -1 (2+x)

User Daniel Apt
by
4.9k points
1 vote

Answer:

-1(2+x)

Explanation:

in the initial equation the -1 was distributed, this answer creates a product (multiplication). -1(2+x)= -2-x

User Kit Ramos
by
4.8k points